Fine-tuned modulation of competitive behaviour according to kinship in barn swallow nestlings - Boncoraglio, Giuseppe (The Royal Society, 2009)
Kin selection theory predicts that, in species where progeny members compete for limiting parental care, individual offspring should be more prone to monopolize parental resources as their genetic relatedness to brood competitors decreases. Mixed parentage among broodmates may arise as a consequence, for example, of extra-pair fertilization or brood parasitism events. In this experimental study of barn swallows (Hirundo rustica), we reciprocally partially cross-fostered hatchlings between broods and compared the behaviour of pairs of related and unrelated broodmates in a competitive context, both under normal food provisioning regime and after mild food deprivation. We found that scramble competition for food mediated by visual and vocal solicitation displays (begging) is inversely related to relatedness among competitors, independent of their level of satiation. Nestlings may modulate their competitive behaviour according to vocal cues that vary with their origin and allow kin recognition. We also uncover direct fitness costs to both parents and offspring arising from mixed parentage in a brood, in terms of increased parental workload and reduced survival of the nestlings. Such previously neglected costs may select for reduced frequency of extra-pair fertilizations and brood parasitism in species with extensive parental care.